Cyclic Vomiting Syndrome: An underdiagnosed entity. Report of a case - Rodríguez, Florencia (2023)
Cyclic vomiting syndrome is a benign, chronic, functional gastrointestinal pathology that manifests clinically with intense nausea and vomiting interspersed with asymptomatic periods. Its diagnosis is made according to the Rome IV criteria, which require the presence of at least 2 episodes of vomiting in the past 6 months or 3 or more episodes in the past year, with the corresponding exclusion of secondary causes that can explain the vomiting. We present the case of a 44-year-old man who consulted for intermittent nausea and vomiting of 1 year evolution with hydroelectrolytic repercussion and multiple emergency consultations. The diagnosis of cyclic vomiting syndrome was made and treatment with amitriptyline was started due to odulatory effect to prevent the recurrence of episodes. After 6 months of establishing it, the patient is asymptomatic.